EFEKTIVITAS MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA KELAS VIII PADA MATERI ZAT ADITIF DI MTS NEGERI GRESIK - Umroh, Ni’matul; Indayati, Tatik (Kohesi: Jurnal Sains dan Teknologi, 2024)
This study aims to analyze the effectiveness of the CORE (Connecting, Organizing, Reflecting, Extending) learning model on the learning outcomes of class VIII students on additive material at MTs Negeri Gresik in the 2024/2024 academic year which is motivated by the difficulties of student learning outcomes. The research method used is a quasi-experimental design with a pre-test post-test control group design. The population of the study was all class VIII students at MTs Negeri Gresik. The sample used was class VIII-B as the experimental class with a total of 36 students and class VIII-A as the control class. The subjects of this study were class VIII A students with a total of 36 students who were taken using the cluster random sampling technique. The data collection technique used a test to measure student learning outcomes. This study uses a data analysis technique for testing the validity of the test sheet through expert judgment, normality test, hypothesis test, and n-gain test. Results of the experimental class hypothesis test. The results of the study showed a significant increase in student learning outcomes in the experimental class compared to the control class. The average pretest sCORE in the experimental class was 43.6111 while the posttest sCORE increased to 82.3611 with a difference in n-gain value of 0.2917. This shows that the CORE learning model is effective in improving students' learning outcomes on additive material. Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) terhadap hasil belajar peserta didik kelas VIII pada materi zat aditif di MTs Negeri Gresik tahun pembelajaran 2024/2024 yang dilatarbelakangi karena adanya kesulitan hasil belajar peserta didik. Metode penelitian yang digunakan kuasi eksperimen dengan desain pretest posttest control group design. Populasi penelitian yaitu seluruh peserta didik kelas VIII di MTs Negeri Gresik. Sampel yang digunakan kelas VIII-B sebagai kelas eksperimen dengan jumlah 36 peserta didik dan kelas VIII-A sebagai kelas kontrol Subjek penelitian ini yaitu peserta didik kelas VIII A dengan jumlah 36 peserta didik yang diambil dengan menggunakan teknik cluster random sampling.Teknik pengumpulan data menggunakan tes untuk mengukur hasil belajar peserta didik. Penelitian ini menggunakan teknik analisis data uji validitas lembar tes melalui expert judgement, uji normalitas, uji hipotesis, dan uji n-gain. Hasil uji hipotesis kelas eksperimen, hasil penelitian menunjukkan adanya peningkatan signifikan pada hasil belajar peserta didik di kelas eksperimen dibandingkan kelas kontrol. Nilai rata-rata pretest di kelas eksperimen adalah 43,6111 sementara nilai posttest meningkat menjadi 82,3611 dengan perbedaan nilai n-gain sebesar 0.2917 hal tersebut menunjukkan bahwa model pembelajaran CORE efektif dalam meningkatkan hasil belajar peserta didik pada materi zat aditif.